Comparison of the Catch of Mangrove Crab (Scylla serrata) Based on Differences in Bait on Rakkang Traps in Selayar Islands Regency - Mutma'innah Hasan; Andi Assir Marimba; Mahfud Palo; Mukti Zainuddin; M. Abduh Ibnu Hajar (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2025)
Mangrove crab (Scylla serrata) is an economically important fishery resource widely distributed across Indonesian waters and strongly associated with mangrove ecosystems, shallow coastal zones, and muddy intertidal habitats. As demand for mud crab continues to increase in both domestic and export markets, improving fishing efficiency through the selection of effective bait becomes essential, particularly for small-scale fisheries operating in mangrove areas. However, bait performance may vary depending on availability, attractiveness, and cost, and information comparing commonly used baits remains limited. This study evaluated the effectiveness of two bait types; stingray bait and chicken waste bait in capturing S. serrata using rakkang traps (Bubu Rakkang). A case study approach was applied by operating a single fishing gear type under comparable field conditions. Primary data were collected directly from trap catches using both bait treatments. Differences in catch performance between traps baited with stingray and those baited with chicken waste were analyzed using a paired (dependent) t-test to account for matched sampling conditions. The results showed no significant difference in mud crab catches between the two bait treatments, indicating that both stingray bait and chicken waste bait were equally effective in attracting and capturing S. serrata. These findings suggest that chicken waste can serve as a practical alternative to stingray bait, offering a potentially more accessible and cost-efficient option for fishers without compromising catch outcomes. The use of low-cost bait sources may contribute to improving the economic feasibility of mud crab fisheries in mangrove ecosystems while supporting sustainable utilization of locally available resources. Further studies are recommended to assess bait effectiveness across different seasons, tidal conditions, and size classes of S. serrata to strengthen management and operational recommendations for rakkang trap fisheries.